2010
DOI: 10.1017/s0007485309990575
|View full text |Cite
|
Sign up to set email alerts
|

How does heat shock affect the life history traits of adults and progeny of the aphid parasitoidAphidius avenae(Hymenoptera: Aphidiidae)?

Abstract: Because insects are ectotherms, their physiology, behaviour and fitness are influenced by the ambient temperature. Any changes in environmental temperatures may impact the fitness and life history traits of insects and, thus, affect population dynamics. Here, we experimentally tested the impact of heat shock on the fitness and life history traits of adults of the aphid parasitoid Aphidius avenae and on the later repercussions for their progeny. Our results show that short exposure (1 h) to an elevated temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 38 publications
5
83
5
Order By: Relevance
“…The +5°C heat pulse, however, had a positive effect on parasitoids as they developed into larger adults that reached adulthood faster. This supports previous work that suggests that extremely high temperatures usually have a negative effect on insects [21, 40, 41], whereas moderate fluctuations may have a neutral or a beneficial effect on them [40, 42]. …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The +5°C heat pulse, however, had a positive effect on parasitoids as they developed into larger adults that reached adulthood faster. This supports previous work that suggests that extremely high temperatures usually have a negative effect on insects [21, 40, 41], whereas moderate fluctuations may have a neutral or a beneficial effect on them [40, 42]. …”
Section: Discussionsupporting
confidence: 91%
“…Short exposure to temperatures above the optimum (i.e. a heat shock) can lead to slower development of immature stages [19] and reduced survival, longevity and fecundity in adults [20, 21]. The negative effects of thermal stress can carry over different life stages [19, 20] and they can even have a transgenerational effect (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to patterns for stressed H. armigera [12], D. melanogaster [11], [15], and Bicyclus anynana [43], we found effects on fertility immediately after heat exposure rather than after a few days. Heat exposure in females and males has previously been shown to strongly affect the reproductive fitness of various insect species [15], [44][49]. Some studies have found that heat stress leads to sterilized eggs through effects on male spermatogenesis [46], which may be more thermosensitive than oogenesis [50].…”
Section: Discussionmentioning
confidence: 99%
“…Short term stress exposures have been used to explore the thermal stress effects on the egg stage [12], although these types of studies do not consider the effects of daily fluctuations that might lead to cumulative effects through injury when stressful low night temperatures are followed by stressful daytime temperatures [13], [14]. In some relevant studies, changes to temperature regimens involved both means and fluctuating ranges simultaneously [15], making it hard to separate out the effects of fluctuations per se .…”
Section: Introductionmentioning
confidence: 99%